2017
DOI: 10.18632/oncotarget.18847
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of selected safety endpoints in phase 1 and late-phase clinical trials of anti-PD-1 and PD-L1 inhibitors: prediction of immune-related toxicities

Abstract: PurposeAnti-PD1 and PD-L1 antibodies are associated with immune-related adverse effects (irAEs). This analysis aims to assess the discrepancies between frequencies of irAEs observed in phase 1 trials with those seen in late-phase trials and to evolve the field of drug development.MethodsPubMed search was conducted for articles published until December of 2016. Trials needed to have at least one of the study arms consisting of nivolumab, pembrolizumab or atezolizumab monotherapy. Trials were matched based on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…With regard to ICI, the authors of a study of 25 trials of antiprogrammed cell death protein 1 (PD-1) or anti-programmed cell death 1 ligand 1 (PD-L1) antibodies, including 6,473 patients, found that, in trials with >118 patients, the incidence of toxicities reported in early phase trials was consistent with that observed for the same agent in later phase trials (P = 0.048) 60 . The only common toxicity that was reported more often in later-phase studies was colitis (P = 0.045) 60 .…”
Section: [H1] Incidence Of Toxicitiesmentioning
confidence: 78%
“…With regard to ICI, the authors of a study of 25 trials of antiprogrammed cell death protein 1 (PD-1) or anti-programmed cell death 1 ligand 1 (PD-L1) antibodies, including 6,473 patients, found that, in trials with >118 patients, the incidence of toxicities reported in early phase trials was consistent with that observed for the same agent in later phase trials (P = 0.048) 60 . The only common toxicity that was reported more often in later-phase studies was colitis (P = 0.045) 60 .…”
Section: [H1] Incidence Of Toxicitiesmentioning
confidence: 78%
“…The cases that we currently present are the first where PD-L1 = 100% with DAKO has been observed along with abscess which we attribute to the connection of pembrolizumab and the high expression of PD-L1. The adverse effects of immunotherapy have been previously well described, however; we have still many to observe [17] , [18] , [19] , [20] . We have observed small differences between the Bio Care kit clone CAL10 and the 22C3 pharmDx™ Kit, DAKO expression.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, new effective antitumor treatments should be urgently developed. [9][10][11][12] Therefore, one considerable strategy is to improve the efficacy of immunotherapeutic drugs and reduce their side effects. For example, the success of immune checkpoint inhibitors, such as antiprogrammed death (PD-1)/programmed death-ligand 1 (PD-L1) and anticytotoxic T lymphocyte-associate antigen-4 (anti-CTLA-4) antibodies, have substantially promoted the development of oncology treatments.…”
Section: Introductionmentioning
confidence: 99%
“…8 Moreover, immune side effects, including the cascade effect of inflammatory mediators, hematopoietic system dysfunction, organ toxicity and rapid emergence of drug resistance, have limited the clinical optimization of these methods. [9][10][11][12] Therefore, one considerable strategy is to improve the efficacy of immunotherapeutic drugs and reduce their side effects.…”
Section: Introductionmentioning
confidence: 99%